2003
DOI: 10.1016/j.ajkd.2003.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentation and outcome of severe acute respiratory syndrome in dialysis patients

Abstract: There was a major outbreak of severe acute respiratory syndrome (SARS) affecting more than 300 patients occurring in a private housing estate in Hong Kong, in which an infected renal patient was suspected to be the primary source. It is unknown whether renal patients would represent a distinct group of patients who share some characteristics that could predispose them to have higher infectivity. In this context, we have encountered 4 dialysis patients contracting SARS in a minor outbreak, which involved 11 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
25
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 8 publications
0
25
0
1
Order By: Relevance
“…It has been speculated that a patient having renal failure might carry an extraordinarily high viral load of SARS, which could lead to a large outbreak. 14 Kwan et al 15 reported that dialysis patients have a higher rate of contracting SARS (1.72%) compared with the general population (0.003% in Hong Kong), but the degree of disease severity, and the mortality rate of the dialysis group was similar to the control group. Given the fact that SARS-CoV-2 has up to 85% sequence similarity with SARS, 16 we should be alert to the possibility that the epidemiologic and clinical characteristics of COVID-19 could follow the same trend as SARS in patients undergoing MHD.…”
Section: Discussionmentioning
confidence: 99%
“…It has been speculated that a patient having renal failure might carry an extraordinarily high viral load of SARS, which could lead to a large outbreak. 14 Kwan et al 15 reported that dialysis patients have a higher rate of contracting SARS (1.72%) compared with the general population (0.003% in Hong Kong), but the degree of disease severity, and the mortality rate of the dialysis group was similar to the control group. Given the fact that SARS-CoV-2 has up to 85% sequence similarity with SARS, 16 we should be alert to the possibility that the epidemiologic and clinical characteristics of COVID-19 could follow the same trend as SARS in patients undergoing MHD.…”
Section: Discussionmentioning
confidence: 99%
“…A wide range of nonrespiratory symptoms has subsequently been reported suggesting other organ involvements including the liver and gastrointestinal tract during the course of the disease [4,10,11]. With the exception of a few chronic dialysis patients complicated by SARS [12][13][14], impaired renal function with raised plasma creatinine is not a common finding in most SARS patients at the time of first clinical presentation. A preliminary study of 12 patients with SARS who developed ARF reports a high mortality rate of 77% [abstract; Tsai HB, et al, J Am Soc Nephrol 14:513A, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…At presentation, patients on dialysis exhibit similar symptoms (fever, myalgia, chills and rigors, gastrointestinal symptoms) as the nondialysis patients (1). However, it is our impression that dialysis patients tend to have less pronounced symptoms (8,9), which may be difficult to distinguish from uremic symptoms. In addition, dialysis patients tended to seek medical attention at a later stage, which might cause a delay in diagnosis and treatment.…”
Section: Discussionmentioning
confidence: 99%